Análisis de las políticas y resultados en el Ecuador: Educación intercultural bilingüe entre 2008 y 2009. - Vinueza Guillén, Marcelo Alexandro (2025)
The research work, entitled “Analysis of policies and results in Ecuador: Intercultural Bilingual Education between 2008 and 2009”, aimed to analyze public policies and results in the field of Intercultural Bilingual Education (IBE) in Ecuador during this period. It addressed a significant number of criteria related to Intercultural Bilingual Education in Ecuador, where the conception of education presents very interesting and innovative elements. However, in the specific case of this research, the time period established is from 2008 to 2009. The methodology used is of a mixed type, with a questionnaire and interviews. The elements of the questionnaire were assessed in order to obtain a truer representation of the results and some news and academic articles were also used to better delimit and evidence the problem under investigation. Finally, the results point to an efficient education at a theoretical level, but with deficiencies in real practice, motivated by a large number of elements that cannot be overlooked, among them, teacher preparation, accessibility to certain rural areas and others that were evidenced by identifying the educational policies applied to IBE.